2020
DOI: 10.1038/s41467-020-19115-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of telomerase inhibition by oxidized and therapeutic dNTPs

Abstract: Telomerase is a specialized reverse transcriptase that adds GGTTAG repeats to chromosome ends and is upregulated in most human cancers to enable limitless proliferation. Here, we uncover two distinct mechanisms by which naturally occurring oxidized dNTPs and therapeutic dNTPs inhibit telomerase-mediated telomere elongation. We conduct a series of direct telomerase extension assays in the presence of modified dNTPs on various telomeric substrates. We provide direct evidence that telomerase can add the nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Another class of molecules that affect telomerase activity include nucleoside analogs such as 6-thio-2’-deoxyguanosine (6dG), didanosine (ddITP), azidothymidine (AZT-TP), and 5-fluro-2’deoxyuridine (5-FdU). These compounds when incorporated at the telomeric ends by telomerase leads to chain termination and uncapping of the telomeric ends ( 94 ). Uncapping by nucleoside analogs prevents binding of the shelterin complex, thereby activating DDR.…”
Section: Telomeres and Telomerase Targeted Cancer Therapiesmentioning
confidence: 99%
“…Another class of molecules that affect telomerase activity include nucleoside analogs such as 6-thio-2’-deoxyguanosine (6dG), didanosine (ddITP), azidothymidine (AZT-TP), and 5-fluro-2’deoxyuridine (5-FdU). These compounds when incorporated at the telomeric ends by telomerase leads to chain termination and uncapping of the telomeric ends ( 94 ). Uncapping by nucleoside analogs prevents binding of the shelterin complex, thereby activating DDR.…”
Section: Telomeres and Telomerase Targeted Cancer Therapiesmentioning
confidence: 99%
“…Telomerase can also insert 2-OH-dATP, but this addition impairs telomere lengthening by interfering with telomerase translocation. Even the telomerase repeat addition processivity factor POT1-TPP1 is unable to rescue the 8-oxo-dGTP or 2-OH-dATP inhibition of telomerase extension (Sanford et al, 2020). Consistent with oxidized dNTPs inhibiting telomerase, MTH1 depletion in telomerase expressing cancer cells with short telomeres causes telomere loss and dysfunction, and apoptosis (Fouquerel et al, 2016).…”
Section: Mth1 Function In Removal Of Oxidatively Damaged Dntps At Telomeresmentioning
confidence: 96%
“…Tenofovir is a nucleoside antiretroviral drug that acts by inhibiting the reverse transcriptase enzyme [118]. Tenofovir also inhibits the activity of human telomerase [119], a crucial enzyme for tumorigenesis and cancer proliferation, whose inhibition represents a promising therapeutic strategy in cancer treatment [120,121]. Sherif et al demonstrated that rats receiving tenofovir at a dose of 50 mg/kg for 24 weeks had diminished colorectal cell proliferation attributed to decreased Bcl-2 and cyclin D1 expression [60].…”
Section: Anti-retroviral Drugsmentioning
confidence: 99%